Клопы – Мириды (heteroptera: miridae) южного Приаралья - Абдуллаева, Д.К; Сапаров, А.Д (SCIENCE and SOCIETY, 2026)
This article provides a general overview of the faunistic study of the Miridae family (hemipterans) in the southern Aral Sea region. A total of 45 species from 22 genera were collected and identified. The author has compiled a catalog of the Miridae families of hemipteran insects in Karakalpakstan, and for the Miridae family, the catalog is currently being completed. Therefore, the aim of this article is to provide a faunistic overview of Miridae in Karakalpakstan.
Keywords: Hemiptera; Miridae; fauna; Southern Aral Sea region